Validation of the Polish version of the Parental Burnout Assessment (PBA). Issue 174 (17th November 2020) - Szczygieł, Dorota; Sekulowicz, Malgorzata; Kwiatkowski, Piotr; Roskam, Isabelle; Mikolajczak, Moïra
Abstract: This study examined the factorial structure of the Polish version of the Parental Burnout Assessment (PBA‐PL) and its relation with other variables, previously shown to be antecedents or outcomes of parental burnout. The PBA‐PL was administered to a total sample of 2, 130 parents along with other instruments depending on the study. Factorial analyses of the PBA‐PL supported both the original four‐factor model of parental burnout (exhaustion related to parenting, feelings of being fed up with parenting, emotional distancing from one's children, and contrast with previous parental self) and a second‐order model with a global parental burnout underlying the four first‐order factors. Both subscale and global scores were reliable. Significant correlations were found between PBA‐PL and neuroticism, emotional intelligence, maladaptive perfectionism, perceived social support, depressive symptoms, marital satisfaction, and life satisfaction. PBA‐PL also predicted both parental neglect and parental violence beyond socio‐demographic factors, depression, and job burnout.